Biotividade de extratos e frações das folhas da Eugenia uniflora L. e da Hyptidendron canum (Pohl ex Benth.) Harley em microrganismos (Bactérias e fungo) e em Oreochromis nilotius - FIUZA, Tatiana de Sousa (2009)
The purpose of this work is to perform the pharmacognostic studies of the species Hyptidendron canum (Pohl ex Benth.) Harley (Lamiaceae) and Eugenia uniflora L. (Myrtaceae), investigate the population variability of the constituents of the essential oil from H. canum leaves and inflorescences, and assess the bioactivity of the crude ethanol extracts and fractions from leaves of this plants against microorganisms (bacteria and the fungus Candida albicans) and on Oreochromis niloticus Linnaeus. For the variability study of the H. canum essential oil, samples obtained from leaves and inflorescences from Hidrolândia, Silvânia, Bela Vista and Goiânia cities were analyzed by gas chromatography and gas chromatography with mass spectrometry. The anatomic analysis and the phytochemical screening of the leaves from the two species were performed using conventional techniques. The antimicrobial activity was assessed with Gram-positive and Gram-negative bacteria and with the Candida albicans fungus using the well diffusion test and the agar dilution method to determine the minimal inhibitory concentration (MIC). The biological activities of the crude ethanol extract and ethyl acetate, hexanic and chloroformic fractions of the leaves from the two species were tested in O. niloticus fish hepatopancreas and gill. The H. canum essential oils analysis indicated high chemovariability in the oils from different locations. The phytochemical screening and the thin layer chromatography (TLC) analysis of the H. canum leaves evidenced the presence of flavonoids, saponins, terpenes and lignans, while the E. uniflora leaves evidenced the presence of tannins, steroids, triterpenes, anthraquinonic heterosides, saponinic and flavonoids. As for the antimicrobial activity testing, the crude ethanol extracts from both species presented antimicrobial activity against all the microorganisms tested and the E. uniflora ethyl acetate fraction presented satisfactory activity against resistant Pseudomonas aeruginosa. The H. canum crude extract and fractions presented vasoactive activity in the hepatopancreas and gill of the tilapias, causing varying degrees of vasodilation and vascular congestion. An apparent proliferation of blood capillaries was detected in the hepatopancreas of the fish that ingested the hexanic fraction. The E. uniflora crude extract and the ethyl acetate, chloroform and hexanic fractions caused vasodilation, vascular congestion and tissue alterations in the O. niloticus hepatopancreas and gills